On-Demand Ultra-Dense Cloud Drone Networks: Opportunities, Challenges and Benefits; IEEE Communications Magazine; Vol. 56, iss. 6 - Sharma N. Navudey; Magarini M. Maurizio; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Sharma V. Vishal; Li Dzhun (2018, 2018)
Title screen